2019
DOI: 10.1556/168.2019.20.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Wing asymmetry of a butterfly community: is altitude a source of stress?

Abstract: We present a novel analysis of fluctuating asymmetry (FA) for butterfly wings at the community-level, along an altitudinal gradient. FA is an important biomonitoring tool that detects deviations of perfect symmetry in bilateral characters, assuming that genetic and/or environmental factors can be a source of stress. This study evaluated the effects of increased altitude on the symmetry of butterfly wings, testing the hypothesis that FA should increase with increased elevation in a tropical mountain. Butterflie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…We measured flying traits of a total of 342 butterflies, belonging to 30 species (Figure SI‐1) of the families Nymphalidae ( S = 15, N = 158), Hesperiidae ( S = 6, N = 88), Pieridae ( S = 5, N = 70), Lycaenidae ( S = 2, N = 18) and Papilionidae ( S = 2, N = 8). Because in a previous study this same butterfly community exhibited wing asymmetry (Henriques & Cornelissen, 2019), we opted to take measurements for wing traits for both the right and left forewings, taking the average of both wings as trait descriptors. We selected seven functional traits that could be measured for the entire community, regardless of species‐specific characteristics: wing length, wing width, wing area, thorax volume, wing:thorax ratio (WTR) length , WTR width and WTR area .…”
Section: Methodsmentioning
confidence: 99%
“…We measured flying traits of a total of 342 butterflies, belonging to 30 species (Figure SI‐1) of the families Nymphalidae ( S = 15, N = 158), Hesperiidae ( S = 6, N = 88), Pieridae ( S = 5, N = 70), Lycaenidae ( S = 2, N = 18) and Papilionidae ( S = 2, N = 8). Because in a previous study this same butterfly community exhibited wing asymmetry (Henriques & Cornelissen, 2019), we opted to take measurements for wing traits for both the right and left forewings, taking the average of both wings as trait descriptors. We selected seven functional traits that could be measured for the entire community, regardless of species‐specific characteristics: wing length, wing width, wing area, thorax volume, wing:thorax ratio (WTR) length , WTR width and WTR area .…”
Section: Methodsmentioning
confidence: 99%
“…Despite the consistent trend across species over time, we note that unexplained variance in FA remains. This could be due to differences in local habitat or microclimate (Henriques & Cornelissen, 2019; Kark, 2001; Schmeller et al, 2011) or other stressful conditions, which could interact in non‐additive ways (Zaragoza‐Trello et al, 2021). Alternatively, variance in FA could also be influenced by the positioning of wings on museum specimens.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we showed that permanent harshness in the form of elevational‐driven stress (Lobregat et al ., 2018; Henriques & Cornelissen, 2019), favours macro‐symbioses within N. coxipoensis nests. Moreover, we provide strong evidence that, in addition to small‐scale abiotic factors (see Cristaldo et al ., 2012), large‐scale ones may also play a definitive role in termitaria invasion by termitophiles.…”
Section: Discussionmentioning
confidence: 99%
“…High‐montane systems provide a natural experiment for the effects of permanent harshness and SGH, because elevation increments show a strong correlation with environmental stress increments. Moreover, providing that such gradients are bound to determine species interactions (Callaway et al ., 2002; Henriques & Cornelissen, 2019) these gradients may ultimately drive termitaria cohabitation. The Espinhaço Mountain Range in Brazil seems particularly suitable to test such a hypothesis (Silveira et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%